DESKRIPSI KESIAPAN GURU DALAM MENGINTEGRASIKAN LITERASI DIGITAL DI SEKOLAH DASAR - Khatimah, Husnul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the readiness of teachers in integrating digital literacy in elementary schools, especially at SDN 142 Borong Ampirie. In the ever-growing digital era, digital literacy is an important competency for teachers to support an effective learning process that is in line with the times. The method used in this research is a qualitative approach with data collection through semi-structured interviews with teachers at the school. The research subjects in the study at SDN 142 Borong Ampirie were grade 1, 4, and 6 teachers as representatives of each grade phase. The results showed that the majority of teachers have a good understanding of digital literacy, but still face challenges in its application, such as limited facilities and infrastructure, and variations in digital competence among teachers. This study recommends the need for continuous training for educators and support from the school to improve teachers' readiness in integrating digital literacy, so that it can facilitate students in facing challenges in the digital era.